Discussion on Water Dew Point and Hydrocarbon Dew Point of Natural Gas. Issue 3 (February 2021) - Zou, Xiaomei; Huang, Fengxia; Zhang, Liming; Gele, Tumeng
Abstract: During natural gas processing and gathering and transportation, water dew point and hydrocarbon dew point as two of control parameters in natural gas because of safety, economy and efficiency etc. In the field chilled mirror manual visual method always be taken to measure water and hydrocarbon dew point due to online instrument test under a differential condition from the pipeline. For hydrocarbon dew point, there're some assays have implied that heavier components in natural gas have an important effect on hydrocarbon dew point, at the same time hydrocarbon dew point gained under the pressure between 2MPa~4MPa is equal to the max condensation temperature which has a practical meaning. On the other hand, the retrograde condensation cannot be ignored; for water dew point, application of molecular sieve would make dew point measurement easier, while application of dehydrating agents such as methanol; glycols and glycerol could cause interference, instruments &operators differences are exist, but the changing process is consistent when chilled down temperature. In this case, Attention should be given to a white fog which might appear on the center of the surface of the chilled mirror one or more times while temperature dropping down. At last some suggestions are given from two aspects of processing and measurement of water and hydrocarbon dew point.